If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3(2 + -3) = 20 Combine like terms: 2 + -3 = -1 2x + -3(-1) = 20 Multiply -3 * -1 2x + 3 = 20 Reorder the terms: 3 + 2x = 20 Solving 3 + 2x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 20 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 20 + -3 2x = 20 + -3 Combine like terms: 20 + -3 = 17 2x = 17 Divide each side by '2'. x = 8.5 Simplifying x = 8.5
| -21+25+(-14)=-10 | | -7x-4=1-8x | | 4-x=2x+25 | | X+(2x+0.15)+(x+.05)=1.8 | | 7(2n-5)-2=-(3n+3) | | 7a+8ab+6b= | | 59+13=91-X | | 2y+7=-3y^2 | | 7n=60+5n | | 9(x+1)-(4x-7)=3 | | -5(4r-5)=25-3r | | 18+8d+d+3d= | | 9-3x+18=54 | | 2t-2=4-t | | -6*8=n+4*2 | | 10p-2(x+50)-6=0.4(3x+20) | | 3x^2=x+10 | | -12n+18=-11n-18 | | 6x^2-7x-3=-8x-1 | | 28z=-5 | | 2y=-4x-10 | | 3e^4t=7e^3t | | -26-10.2x=-21(-0.9x+4) | | 9p-6q=33 | | f(-3)=e^9x | | x-3=13+1-2x-8 | | x-0.17x=539.09 | | -3+7p=-9+6p | | -2y-8=4y+22 | | y=3x-5-11 | | h^2-2h+1=0 | | -9.84=2.6+0.4x |